2023
DOI: 10.1038/s41420-023-01490-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the effect of magnetic iron oxide nanoparticles on cells and extracellular vesicles

Abstract: At present, iron oxide nanoparticles (IONPs) are widely used in the biomedical field. They have unique advantages in targeted drug delivery, imaging and disease treatment. However, there are many things to pay attention to. In this paper, we reviewed the fate of IONPs in different cells and the influence on the production, separation, delivery and treatment of extracellular vesicles. It aims to provide cutting-edge knowledge related to iron oxide nanoparticles. Only by ensuring the safety and effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 125 publications
1
9
0
1
Order By: Relevance
“…Herein, we investigated the potential of ferumoxytol, our FDA-approved iron oxide nanoparticle (IONP) commonly used for iron supplementation in patients and as MRI contrasts in angiography, to enhance the homing capabilities of MSCs in the treatment of myocardial infarction. Once endocytosed by MSCs, ferumoxytol is trapped in acidic intracellular lysosomes (pH 4.5), where it degrades and releases iron ions. Intriguingly, we found that these iron ions induced an intracellular hypoxic environment, stabilize HIF-1α, a critical factor in postimplantation MSC migration. As has been reported by we and others, the degradation of ferumoxytol within lysosomes, which occurs over approximately one month, , does not affect iron homeostasis.…”
mentioning
confidence: 75%
“…Herein, we investigated the potential of ferumoxytol, our FDA-approved iron oxide nanoparticle (IONP) commonly used for iron supplementation in patients and as MRI contrasts in angiography, to enhance the homing capabilities of MSCs in the treatment of myocardial infarction. Once endocytosed by MSCs, ferumoxytol is trapped in acidic intracellular lysosomes (pH 4.5), where it degrades and releases iron ions. Intriguingly, we found that these iron ions induced an intracellular hypoxic environment, stabilize HIF-1α, a critical factor in postimplantation MSC migration. As has been reported by we and others, the degradation of ferumoxytol within lysosomes, which occurs over approximately one month, , does not affect iron homeostasis.…”
mentioning
confidence: 75%
“…Nanomedicine is an important component of nanotechnology, which is mainly used for medical diagnostics and drugs delivery [ 1 ]. Magnetite (Fe 3 O 4 ), hematite ( α -Fe 2 O 3 ), maghemite ( γ -Fe 2 O 3 ), and mixed ferrites are considered to be the main representative of iron oxide nanoparticles (IONPs) [ 2 ]. Due to their well-biocompatibility, fine biodegradability, low toxicity, and strong magnetism, IONPs have been widely employed in the biomedical fields, such as magnetic resonance imaging (MRI), targeted drug delivery, cancer immunotherapy and hyperthermia mediators (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…24−27 This approach also eliminates the need for organic solvents, thus improving the overall safety and efficacy of the drug delivery. Dendronized polymers, 28 liposomes, 29−31 polymer micelles, 32 polymer-drug conjugates, 33,34 polymer vesicles, 35,36 carbon nanotubes, 37,38 silica nanoparticles, 39−41 iron oxide nanoparticles, 42,43 gold nanoparticles, 44−46 etc., have all been investigated as nanocarriers. Among them, polymer micelles, liposomes, and polymer-drug conjugates are perceived as the most promising candidates and have received a great deal of interest in fundamental research and even clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocarriers have aroused a great deal of interest in the diagnostic and therapeutic treatment of cancer. In particular, theranostic nanosystems have been realized on nanocarriers by binding both active drug ingredients and disease detection components through covalent bonds, weak interactions, and other physical means. By utilizing tumor-specific phenomena and interactions, namely, an enhanced permeability and retention (EPR) effect, , specific ligand binding, and an endogenous microenvironment and exogenous stimuli, , these nanosystems are able to target the lesion site and release the therapeutic agents in a responsive manner. , As a result, targeted nanosystems exhibit superior performance over single drug or single detection component systems at the same dose. For example, the solubility of hydrophobic drugs such as paclitaxel, camptothecin, docetaxel, and others is significantly improved when uploaded into micellar nanocarriers. This approach also eliminates the need for organic solvents, thus improving the overall safety and efficacy of the drug delivery. Dendronized polymers, liposomes, polymer micelles, polymer-drug conjugates, , polymer vesicles, , carbon nanotubes, , silica nanoparticles, iron oxide nanoparticles, , gold nanoparticles, etc ., have all been investigated as nanocarriers. Among them, polymer micelles, liposomes, and polymer-drug conjugates are perceived as the most promising candidates and have received a great deal of interest in fundamental research and even clinical studies .…”
Section: Introductionmentioning
confidence: 99%